2002
DOI: 10.1086/342869
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Evolution in Our Galaxy during the Last 5 Gyr

Abstract: A significant fraction of the gas in the Galactic disk comes from quasi-continuous infall of external material that is moderately processed by stellar nucleosynthesis. Based on a comparison of the abundances in the protosolar cloud (PSC) and the Local Interstellar Cloud (LIC), we propose that the infalling matter carries the nucleosynthetic signature of dwarf galaxies. The dwarfs have low metallicity, and secondary products of stellar nucleosynthesis are scarce as compared to primary products. Using a simple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…A fraction of the gas will most likely be accreted by the Milky Way providing new fuel for star-formation. The infall of low-metallicity gas on to the Milky Way might solve the so-called G-dwarf problem (see Geiss et al 2002, and references therein). 3.…”
Section: Discussionmentioning
confidence: 99%
“…A fraction of the gas will most likely be accreted by the Milky Way providing new fuel for star-formation. The infall of low-metallicity gas on to the Milky Way might solve the so-called G-dwarf problem (see Geiss et al 2002, and references therein). 3.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the elemental abundances in the Protosolar Cloud (PSC) with those in the LIC and nearby interstellar medium (ISM), Geiss concluded that the composition of matter in the solar ring of the Milky Way could not have evolved from matter with a PSC composition in a closed system environment. To account for the LIC composition Geiss et al (2002) proposed that a significant fraction of the gas in the Galactic disk comes from quasi-continuous infall of low-metallicity material from dwarf galaxies and, using a simple mixing model, showed that the difference found in the LIC and PSC compositions can be explained my this process (see Fig. 19a).…”
Section: Mixing Models and Late Galactic Evolutionmentioning
confidence: 99%
“…14 N is-at least in part-a secondary nucleus, and it is produced in significant amounts in low mass stars. Therefore, in a closed system, the 14 N/ 16 O ratio should increase with time, contrary to measurements that indicate a lower N/O ratio in the LIC than in the PSC (Gloeckler and Geiss 2001;Geiss et al 2002;Gloeckler 2005).…”
Section: Galactic Evolution During the Last 5 Gyrmentioning
confidence: 59%